Exploring family models and SDG number five in picture books. Dialogical alternatives for secondary education - López-Valero, Amando; Hernández-Delgado, Lourdes; Jerez-Martínez, Isabel; Encabo-Fernández, Eduardo (Frontiers in Education, 2025)
IntroductionThis contribution addresses the controversy that often surrounds the educational treatment of new family models. The literature, as a medium of fiction based on reality, reflects social changes, including the organization of families. Promoting gender equality—Sustainable Development Goal (SDG) number five (United Nations)—is closely linked to understanding these new family structures. In this context, picture books—powerful literary resources that combine images and words—should be used to expose students to new realities and raise awareness of diversity, thereby fostering tolerance and respect.MethodThis study analyzes several picture books, including classics like King and King and more recent titles like Well done Mummy. The analysis will focus on their format and content to determine their suitability for secondary school classrooms, discuss family models, and raise awareness, potentially changing attitudes. Following the analysis, we explore how to incorporate these books into educational sequences, highlighting the use of dialogical discussions to promote critical thinking.ResultsThe results of this contribution will include a list of suggested picture books, an evaluation of their suitability, and proposed didactic strategies.DiscussionThese aspects will strengthen the classroom treatment of this controversial topic, helping students grow holistically through axiological aspects and the development of SDG number five: gender equality. Additionally, this study will confirm the relevance of using picture books in the classroom within the context of liquid modernity, where audiovisual elements are key motivators for students.